KEPEMIMPINAN TRANSFORMASIONAL DALAM PERENCANAAN STRATEGIK SEKOLAH BERBASIS MANAJEMEN BERBASIS SEKOLAH - Hidayat, Hidayat; Khamim, Nur; Kurniawati, Nia; Aji Fachrurroji, Fahmi (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to describe the implementation of transformational leadership by school principals in strategic planning based on School-Based Management (SBM). This research adopts a qualitative case study approach, using interviews, observations, and documentation studies as data collection techniques. The findings show that the principal applies key dimensions of transformational leadership, such as inspirational motivation, individualized consideration, and intellectual stimulation, in the formulation of strategic planning. The planning process is conducted through deliberation, data analysis, and stakeholder involvement. The principal acts as a facilitator of innovation and collaboration in designing school programs. These findings indicate that transformational leadership significantly contributes to the quality of SBM-based strategic planning, particularly in aspects of participation, reflection, and accountability.